Effects of pH and Oxygen and Ammonium Concentrations on the Community Structure of Nitrifying Bacteria from Wastewater - Prinčič, Alenka (American Society for Microbiology, 1998)
Shifts in nitrifying community structure and function in response to different ammonium concentrations (50, 500, 1,000, and 3,000 mg of N liter(−1)), pH values (pH 6.0, 7.0, and 8.2), and oxygen concentrations (1, 7, and 21%) were studied in experimental reactors inoculated with nitrifying bacteria from a wastewater treatment plant. The abilities of the communities selected for these conditions to regain their original structures after conditions were returned to the original conditions were also determined. Changes in nitrifying community structure were determined by performing an amplified ribosomal DNA (rDNA) restriction analysis of PCR products obtained with ammonia oxidizer-specific rDNA primers, by phylogenetic probing, by small-subunit (SSU) rDNA sequencing, and by performing a cellular fatty acid analysis. Digestion of ammonia-oxidizer SSU rDNA with five restriction enzymes showed that a high ammonium level resulted in a great community structure change that was reversible once the ammonium concentration was returned to its original level. The smaller changes in community structure brought about by the two pH extremes, however, were irreversible. Sequence analysis revealed that the highest ammonium environment stimulated growth of a nitrifier strain that exhibited 92.6% similarity in a partial SSU rRNA sequence to its nearest relative, Nitrosomonas eutropha C-91, although the PCR product did not hybridize with a general phylogenetic probe for ammonia oxidizers belonging to the β subgroup of the class Proteobacteria. A principal-component analysis of fatty acid methyl ester data detected changes from the starter culture in all communities under the new selective conditions, but after the standard conditions were restored, all communities produced the original fatty acid profiles.